Durable Low‐Interfacial Toughness PDMS/SiO2 Coatings with Superior Anti‐Icing and Large‐Scale Deicing Performance in the Natural Field - Tao Zhu; Yuan Yuan; Xingde Wei; Xujiang Hua; Xu Dai; Huiying Xiang; Linbo Song; Ruijin Liao (Advanced Materials Interfaces)
Abstract Ice accretion on wind turbine blades severely impacts the power generation efficiency, equipment lifespan, and safe operation of wind farms. Low‐interfacial toughness materials have demonstrated potential for large‐scale deicing under controlled laboratory conditions. However, their anti‐icing and deicing performance in complex and harsh natural fields is rarely studied. Herein, low‐interfacial toughness PDMS/SiO2 coatings are prepared on aluminum plates. Field tests for anti‐icing, icephobic, and large‐scale deicing are conducted in the high‐altitude regions of Southwest China. Fortunately, the PDMS/SiO2 coating exhibits exceptional anti‐icing and icephobic properties. The coating effectively delays the freezing of water droplets and natural ice accretion, significantly reducing icing weight and ice adhesion strength. During natural ice‐covering processes, the ultra‐low ice adhesion of the PDMS/SiO2 coating aids in efficient ice shedding through wind and gravity and ensures rapid melting post‐icing. Additionally, the PDMS/SiO2 coating excels in large‐scale deicing performance. The constant deicing force, governed by low interfacial toughness, provides robust assurance for efficient large‐scale deicing of ice layers of varying sizes under gravity. Moreover, the coating demonstrates stable durability, retaining excellent deicing capabilities during icing/deicing cycles, UV radiation, and high‐temperature aging tests. This study lays an experimental foundation for the further research and application of low‐interfacial toughness materials.